Real-time PCR for simultaneous and quantitative detection of quarantine phytoplasmas from apple proliferation (16SrX) group - Torres, E.; Bertolini, Edson; Cambra, Mariano; Monton, C.; Martin, M. P. (2017)
A real time PCR assay conjugated with the fluorescent SYBR(R) Green I dye has been developed for rapid, sensitive and quantitative ;detection of 'Ca. Phytoplasma pyri', 'Co. P. prunorum' and 'Ca. P. mali', quarantine members of apple proliferation (16SrX) group. The selected primers amplify specifically a target of 217-bp fragment from the 16Sr gene region of the 16SrX group and not from any other tested phytoplasma groups. An artificial template consisting in a plasmid clone of a 1785-bp DNA fragment of the 16S rRNA gene, 16S/23S rDNA spacer region, tRNA-Ile and partial 23S rRNA gene of a 'Ca. P. prunorum' isolate, was used to establish a calibration curve to evaluate the number of amplified targets per sample. The sensitivity of the technique was similar to nested-PCR (10 copies of the amplified target per mu l). The estimated concentration of phytoplasmas in infected pear, plum and apricot trees ranged from 9.7 X 10(3) to 3.0 X 10(5) phytoplasmas per gram of tissue. The method offers the possibility to detect simultaneously, in a single reaction, all quarantine phytoplasmas affecting fruit trees hosts in Europe. (C) 2005 Elsevier Ltd. All rights reserved.